Mass Spectrometry-Imaging Analysis of Active Ingredients in the Leaves of Taxus cuspidata - Zhan, Xiaori; Zang, Yue; Ma, Ruoyun; Lin, Wanting; Li, Xiao-lin; Pei, Yanyan; Shen, Chenjia; Jiang, Yan (ACS omega, 2024)
Background: Taxus cuspidata is an endangered evergreen conifer mainly found in Northeast Asia. In addition to the well-known taxanes, several active ingredients were detected in the leaves of T. cuspidata. However, the precise spatial distribution of active ingredients in the leaves of T. cuspidata is largely unknown. Results: in the present study, timsTOF flex MALDI-2 analysis was used to uncover the accumulation pattern of active ingredients in T. cuspidata leaves. In total, 3084 ion features were obtained, of which 944 were annotated according to the mass spectrometry database. The principal component analysis separated all of the detected metabolites into four typical leaf tissues: mesophyll cells, upper epidermis, lower epidermis, and vascular bundle cells. Imaging analysis identified several leaf tissues that specifically accumulated active ingredients, providing theoretical support for studying the regulation mechanism of compound biosynthesis. Furthermore, the relative accumulation levels of each identified compound were analyzed. Two flavonoid compounds, ligustroflavone and Morin, were identified with high content through quantitative analysis of the ion intensity. Conclusions: our data provides fundamental information for the protective utilization of T. cuspidata.